Generation of surface polaritons in dielectric cylindrical waveguides; Physical Review Accelerators and Beams; Vol. 22, iss. 4 - Kotanjyan A. S. Anna; Mkrtchan (Mkrtchyan) A. R. Alpik Rafaelovich; Saharian A. A. Aram; Kotanjyan V. Kh. (2019, 2019)
Title screen